Beyond averages: new approaches to understand heterogeneity and risk of technology success or failure in smallholder farming - Vanlauwe, Bernard; Coe, R.; Giller, Kenneth E. (Cambridge University Press, 2019)
In recent years, many studies have demonstrated the heterogeneity of the smallholder production environment. Yet agronomic research for development (R4D) that aims to identify and test options for increasing productivity has not consistently adapted its approaches to such heterogeneous conditions. This paper describes the challenges facing research, highlighting the importance of variation in evaluating the performance of soil management recommendations, integrating aspects of production risk management within the formulation of recommendations, and proposing alternative approaches to implement agronomic R4D. Approaches are illustrated using two multi-locational on-farm paired trials, each having one no-input control treatment and a treatment with fertilizer application for maize in Western Kenya and for beans in Eastern Rwanda. The diversity of treatment responses should be embraced rather than avoided to gain a better understanding of current context and its relation with past management.